Utilization of different leguminous seeds in the diets of lactating goats. Food intake, digestive utilization of nutrients and nitrogen balances - Ramos E.; De la Torre G.; Fernández J.R.; Gil Extremera F.; Sanz Sampelayo M.R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The leguminous seeds are considered a good protein source for domestic animals. In this study four different leguminous seeds were used as alternative sources of meat meals for lactating goats. Four different diets were designed in which 30% of the total protein content was derived from one leguminous seed, namely: lupine seeds, faba beans, bitter vetch seeds and vetch seeds. Food intake, digestive utilization and nitrogen balance data were derived from the corresponding balance assays. The results obtained revealed the good acceptation and nutritional utilization of the four diets. Lupine seeds were outstanding for energy utilization and faba bean seeds were best for nitrogen utilization.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)